Surveillance for the use of mycophenolate mofetil for adult patients with lupus nephritis in Japan. Issue 6 (8th September 2015) - Yasuda, Shinsuke; Atsumi, Tatsuya; Shimamura, Sanae; Ono, Kota; Hiromura, Keiju; Sada, Kenei; Mori, Masaaki; Takei, Syuji; Kawaguchi, Yasushi; Tamura, Naoto; Takasaki, Yoshinari
Abstract : Objectives. Mycophenolate mofetil (MMF) is used as one of the standard induction/maintenance protocols for lupus nephritis (LN). However, MMF has not been approved for treating LN in any country, resulting in worldwide off-label use of this immunosuppressant. In order to clarify the real-world use of MMF as a treatment for LN in Japan, Japan College of Rheumatology surveyed the use of MMF in daily clinical practice. Methods. Adult patients with LN who visited enrolled hospitals from October 2008 to September 2013 were surveyed for the initial, maximum, and maintenance doses of MMF. The safety and efficacy of MMF were retrospectively evaluated. Results. One hundred and thirty-seven LN patients including 116 females were enrolled. The median of initial, maximum, and maintenance doses of MMF were 1.0 g/day, 1.5 g/day, and 1.0 g/day, respectively. Sixty-one adverse events were reported in 39 patients during the follow-up period. Median urine protein level decreased from 1.89 g/gCr to 0.21 g/gCr, meanC3 level increased from 66.4 mg/dl to 80.3 mg/dl, and median anti-DNA antibody titer decreased from 40.6 IU/ml to 10.6 IU/ml. Conclusion . MMF was commonly used for the treatment of adult LN patients with acceptable efficacy and safety in Japan.